Tools for online collaboration: do they contribute to improve teamwork? - Lopes, I. (2016)
In the last decades, the fast growth of Information and Communication Technologies changed our way to communicate and share information. Traditional groups or teams frequently give way to virtual teams, working with tools for online collaboration. Interaction between persons geographically dispersed has become easier. However, the use of new collaboration tools can also bring many challenges. Some technologies, like e-mail, can create delays on reply or even misunderstandings, case the message is not well understood by the recipient. Can these new technologies improve the productivity and enhance the creativity between group members, improving also their confidence and motivation? Although virtual teams have a high capacity to adapt to constant market changes, personal interactions are still important, mainly to clarify tasks and goals. The main purpose of this study is to understand how tools for online collaboration may improve the productivity (and enhance creativity) in teamwork. This study was conducted through an internet platform and the survey was hosted online by SurveyMonkey.com. We intended to verify, among other questions, what users think about different collaboration tools, how often they use these tools, and how they perceive these technologies as adequate ways to communicate, to work with, and to improve productivity. Findings show that e-mail is the most used tool, and personal contact is still more important for teamwork than any tools for online collaboration. Our results contribute to perceive in what extent collaboration tools are indeed an asset or a barrier in teamwork.